EFFECTS OF LANGUAGE USE THROUGH AN INTEGRATED SKILLS INTERVENTION ON ENGLISH LANGUAGE LEARNERS' SPEAKING SKILLS: A FOCUS ON VOCABULARY AND GRAMMAR - Tulu, Dereje Gebisa; Gutema, Hailu (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
This study examines the effects of language use through a thorough skills intervention on students' general level of speaking skills, focusing on vocabulary and grammar. A quasi-experimental investigation was conducted to fulfill the research objective. The total number of participants was selected by systematic random sampling and divided into control and experimental groups. During the 2022 academic year, 92 Shambu High School of 10th grade students participated in the study. Tests with oral questions were given before and after the intervention and the results were evaluated using SPSS. Independent samples t-test results showed that there was no significant difference between the pretest scores of the two groups on the oral presentation samples, either in general speaking ability or in the use of grammar and vocabulary. However, the general spoken language abilities of the two groups and their consumption of vocabulary and grammatical elements differed significantly in the post-test. According to the paired sample t-test, the experimental group improved their basic speaking skills more than the control group. Therefore, it can be argued that teaching English through an integrated skills intervention had a better impact on students' speaking abilities than a more conventional method of teaching speaking skills. The study found that integrated skill strategies should be used in EFL lecture sessions to help students develop their interpersonal skills